Field screening and identification of biochemical indices of pod borer (Helicoverpa armigera) resistance in chickpea mutants - Noreen, Asima; Hameed, Amjad; Shah, Tariq Mahmud (Frontiers in Plant Science, 2024)
Chickpea pod borer (CPB) (Helicoverpa armigera) is one of the major pests, causing significant yield losses. The objectives were to screen chickpea mutants for pod borer resistance/tolerance under field conditions and identification of biochemical markers of tolerance. Chickpea mutant CM216-A/15 had highest leaf (25 trichomes/mm2) and stem trichome density (17 trichomes/mm2) with least pod damage at Kallur Kot and highest pod weight per plant (22.8 ± 2.6g) at AZRI. Higher total phenolic contents (TPCs) and antioxidant capacity were detected in tolerant mutants, i.e., CM216-A/15 and CM664/15. TPC was positively associated with pod yield and had negative correlation with pod damage. Mutants CM216-A/15, CM664/15, and CM766/15 depicted the highest resilience to CPB, owing to higher hairiness, better antioxidant defense response, and lower levels of hydrolytic enzymes and sugars. Identified biochemical markers like TPC, total oxidant status, superoxide dismutase, and pigments can be used for screening of CPB-tolerant/resistant mutants.